Emotional girls and rational boys: the gendering of violence among urban, African American youth - Like, Toya Z. (Crime & delinquency, 2019)
Much scholarship has given primacy to neighborhood context and its effect on youth violence within disadvantaged communities. The structural features of these environments, including various forms of disadvantage such as extreme poverty, unemployment and family disruption, have resulted in cultural adaptations that embrace the use of violence and the construction of violent identities as a means of survival and protection especially among youth. We adhere to and contribute to this perspective by recognizing the contributions of the symbolic interaction approach that underscores the process by which these identities are constructed. Recent developments in this area have emphasized the intersecting inequalities of race, gender and class that shape individuals’ understandings of and perceptions of violence. We draw on these works and analyze in-depth interviews with 72 urban, African American adolescents to examine the process by which they perceive and negotiate violence (and thus construct violent identities) and we further consider whether these constructions of violence are gender-specific.